Social Determinants and Community Behavior Against Implementation of the Covid-19 Health Protocol: Systematic Review - Purnomo, Teguh; Aji, Budi (Journal La Medihealtico, 2025)
The incidence of coronavirus disease (Covid-19) is the latest challenge facing the international community. Health protocols such as social distancing, wearing masks, washing hands and limiting community activities are implemented in the community to prevent a spike in coronavirus cases. The policy of implementing health protocols in the community results in the community itself not complying with the guidelines. For this reason, researchers conducted research to determine social determinants and explanations of community behavior regarding the implementation of the 2019 coronavirus disease (Covid-19) health protocol. This study used a systematic review design where researchers searched for articles from the Google Scholar and PubMed databases. From the search results, six articles were then considered that met the inclusion criteria. Findings show that community knowledge, education, attitudes and behavior, age and gender influence the implementation of medical procedures related to COVID-19. Factors that influence the implementation of health protocols to prevent the spread of the corona virus disease (Covid-19) in society include awareness of the implementation of health protocols, limited infrastructure, limited health personnel; and public attitudes towards health protocols. Apart from that, behavioral, psychosocial and cognitive factors of the population in accordance with socio-cultural, demographic and health characteristics also influence the implementation of health protocols during the COVID-19 pandemic. The need for community attitudes such as the perception of high risk of COVID-19 encourages individuals to follow health protocols with more discipline, and the existence of social environmental support such as positive social interactions can increase individual motivation to comply with existing rules.